DIALECTICS OF EDUCATIONAL TECHNOLOGY AND REPOSITION ISLAMIC EDUCATION (PAI) TEACHER’S ROLE IN GLOBALIZATION ERA - Agus Purwowidodo (Sayyid Ali Rahmatullah Tulungagung State Islamic University, 2016)
Learning technology as applied disciplines grows and evolves according to the needs of learning: more effective, efficient, spacious, and quickly in the global era. It also facilitates problem solving learning on design aspects, development, utilization, assessment processes and learning resources. Perspective of learning technology in the global era is how Islamic education (PAI) teachers professionally are able to design and create innovative learning environment with reference to the process of national education standard that sets out in the framework of national education. PAI teacher’s challenge in the global erais the demands of the learning process that can improve information literacy that is well supported by data and facts to deliver to the students in the era of information society and the knowledge society. So it is needed an approach and innovative method of learning strategies that address the challenges of learning needs in the globalization and information era. Dialectics of technology on learning in a globalization era are characterized by the demands of the students to have critical thinking skills, problem solving, innovative and creative, mastering ICT, fluent communication and multi languages. And also Islamic education teacher competence and interaction and learning technologies such as ICT products that push reposition the role of an advanced teacher trainer, counselor, manager, participants, leader and author of learning works asan abstraction and a high commitment as a base quality of professionalism.Teknologi pembelajaran sebagai disiplin ilmu terapan tumbuh dan berkembang sesuai kebutuhan belajar yang lebih efektif, efisien, luas dan cepat di era global. Selain itu juga memfasilitasi pemecahan masalah belajar pada aspek desain, pengembangan, pemanfaatan, penilaian proses-proses serta sumber-sumber belajar. Perspektif teknologi pembelajaran di era global adalah bagaimana guru PAI secara profesional mampu mendesain dan menciptakan lingkungan belajar yang inovatif dengan mengacu pada standar proses pendidikan nasional yang ditetapkan dalam kerangkan pendidikan nasional. Tantangan guru PAI di era global adalah tuntutan terhadap proses pembelajaran yang mampu meningkatkan information literacy yang baik didukung oleh data dan fakta untuk mengantarkan siswanya menuju pada era masyarakat informasi dan masyarakat ilmu pengetahuan. Sehingga dibutuhkan pendekatan strategi dan metode inovatif pembelajaran yang mampu menjawab tantangan kebutuhan pembelajaran pada era globalisasi dan informasi. Dialektika teknologi terhadap proses pembelajaran di era global diwarnai dengan tuntutan terhadap siswa mempunyai keterampilan dalam berpikir kritis, memecahkan masalah, inovatif dan kreatif, menguasai ICT, komunikasi lancar, multi bahasa. Serta interaksi kompetensi guru PAI dan produk teknologi pembelajaran berupa ICT yang mendorong reposisi peran guru menjadi pelatih, konselor, manajer, partisipan, pemimpin serta pengarang karya pembelajaran sebagai daya abstraksi dan komitmen yang tinggi sebagai basis kualitas profesionalisme.